The influence of a potential barrier on the mechanisms of excitation of own fluctuations in radio products in conditions of exposure to electromagnetic radiation - Serkov, Aleksandr; Breslavets, Vitalii; Breslavets, Juliya; Yakovenko, Igor (Національний технічний університет "Харківський політехнічний інститут", 2023)
The subject matter is the processes of analysis and the mechanisms of the emergence of their own fluctuations in the semiconductor complex electro -radio devices (communications equipment), if there are currents and voltages entrusted with pulsed electromagnetic radiation, the results obtained in the work of the potential barrier on the border of the semi -conductive structure on the border of the semiconductor (voltage ampere) characteristics of a electroradio device. The aim is model of transforming the energy of the flow of charged particles, induced by external electromagnetic radiation, into the energy of its own fluctuations in the semiconductor structure, taking into account the properties of the structure itself (heterogeneity of potential at the border). The implementation of this model is due to theeffect of transitional radiation of moving charges, when the particle flow crosses the boundary of the media section with various electromagnetic properties (dielectric permeability) and part of its energy is transformed into the energy of its own fluctuations in the semiconductor structure. The objectives are: mechanisms of the strengthening (instability) mode of semiconductor components of semiconductor devices under conditions of impulse electromagnetic radiation in the presence of a potential barrier on the boundary of the media of the media. The methods used are the method of theory of small disturbances, which allows you to determine the spectrum of the own vibrations of the system: the current fluctuations of the semiconductor device in electromagnetic radiation. The following results are obtained: The interaction of surface plasmons with the flow was considered charged particles in the presence of a potential barrier based on energy principle. Kinetic equations have been obtained that determine the change in the number superficial plasmons, expressions for the increments of their instability with taking into account the size of a potential barrier on the border, which leads t o the appearance of a beam reflected from the border. The results of the work allow you to take into account the contribution of the reflected and completed component of the energy flow energy into the total energy of the radiation of surface vibrations. The mechanisms of interaction between the flow of charged particles with the own electromagnetic fluctuations of two -dimensional electronic gas, the occurrence of which is due to the presence of a potential barrier on the border of the media section. Conclusion. Determination of the amplification (generation) modes of electro -radio products that distort their volt are ampere characteristics (reversible failures) depending on the parameters of external electromagnetic radiation. An analysis of the routes obtained in the work can be used in the development of radio emergency for working in a millimeter and submilimeter range (amplifiers, generators and frequency converters). Assessment of indicators of the exponential growth of amplitudes of the own fluctuations of semiconductor components (increement of instability as a criterion of reversible failures) show that the magnitude of the energy of radiation lies within the sensitivity of modern receivers of the radiation of the submilimeter range and is the reason for the failure.

Предметом дослідження є процес аналізу механізмів виникнення нестійкостей власних коливань напівпровідникових комплектуючих електрорадіовиробів (апаратури зв'язку), за наявності струмів і напруг, наведених імпульсним електромагнітним випромінюванням. електрорадіовироби. Метою дослідження є модель трансформації енергії потоку заряджених частинок, наведеного зовнішнім електромагнітним випромінюванням, на енергію власних коливань напівпровідникової структури з урахуванням властивостей самої структури (неоднорідностей потенціалу на кордоні). Реалізація даної моделі обумовлена ефектом перехідного випромінювання зарядів, що рухаються, коли потік частинок перетинає межу розділу середовищ з різними електромагнітними властивостями (діелектричною проникністю) і частина його енергії трансформується в енергію власних коливань напівпровідникової структури. Цілі такі:: механізми режиму посилення (нестійкості) коливань напівпровідникових комплектуючих напівпровідникових приладів в умовах впливу імпульсного електромагнітного випромінювання за наявності потенційного бар'єру на межі розділу середовищ, що комплектують виріб. Методи, що застосовувались при дослідженні: метод теорії малих обурень, що дозволяє визначити спектр власних коливань системи: наведені електромагнітним випромінюванням струми - власні коливання напівпровідникового приладу. Отримано такі результати: Розглянуто взаємодію поверхневих плазмонів із потоком заряджених частинок за наявності потенційного бар'єру, виходячи з енергетичного принципу. Отримано кінетичні рівняння, що визначають зміну числа поверхневих плазмонів, вирази для інкрементів їх нестійкостей з урахуванням величини потенційного бар'єру на кордоні, що призводить до появи відбитих від межі частинок пучка. Результати роботи дозволяють враховувати внесок відбитої та минулої компонент енергії потоку частинок у сумарну енергію випромінювання поверхневих коливань. Досліджено механізми взаємодії потоку заряджених частинок із власними електромагнітними коливаннями двовимірного електронного газу, виникнення якого обумовлено наявністю потенційного бар'єру на межі поділу середовищ. Висновки. Визначення режимів посилення (генерації) коливань електрорадіовиробів, що спотворюють їх вольт - амперні характеристики (зворотні відмови) залежно від параметрів зовнішнього електромагнітного випромінювання. Аналіз результатів, отриманих у роботі, може бути використаний при розробці радіовиробів, що працюють у міліметровому та субміліметровому діапазоні (підсилювачів, генераторів та перетворювачів частоти). Оцінки показників експоненційного зростання амплітуд власних коливань напівпровідникових комплектуючих приладів (інкременту нестійкості як критерію оборотних відмов) показують, що величина енергії випромінювання лежить у межах чутливості сучасних приймачів випромінювання субміліметрового діапазону і є причиною виникнення відмов.
Вплив потенційного бар'єру на механізми порушення власних коливань радіовиробів в умовах впливу електромагнітного випромінювання
Keywords: induced current; electromagnetic radiation; semiconductor components; superficial vibrations; instability of oscillations